Flight Risk The Coalition's Air Advisory Mission in Afghanistan, 2005-2015. - Marion, Forrest L. (Naval Institute Press, 2018)
From the 1920s Afghanistan maintained a small air arm that depended heavily upon outside assistance. Starting in 2005, the United States led an air advisory campaign to rebuild the Afghan Air Force (AAF). In 2007 a formal joint/combined entity, led by a U.S. Air Force brigadier general, began air advisor work with Afghan airmen.